Optical emissivity dataset of multi-material heterogeneous designs generated with automated figure extraction - Viktoriia Baibakova; Mahmoud Elzouka; Sean Lubner; Ravi Prasher; Anubhav Jain (Scientific Data, 2022)
Measurement(s) optical emissivity • device design Technology Type(s) Fourier transform infrared microscopy • text mining